Comparison of spectral responses of Cs2TiI6-XBrX based Perovskite device with CdS and TiO2 Electron transport layer. Issue 1 (February 2021) - Chakraborty, Kunal; Paul, Samrat
Abstract: This article represents the spectral responses of a planar FTO/CdS or TiO2 /Cs2 TiI6 -X BrX /CuSCN/Ag based structure where CdS and TiO2 is used as Electron transport layer (ETL) and CuSCN as Hole transport layer (HTL) under 300 K temperature condition with the SCAPS-1D simulator. The simulation was performed at 750 nm thickness of Cs2 TiI6 -X BrX absorbing material where x = 0 to 6 to understand the quantum efficiency (QE) using two different ETL (CdS and TiO2 ). This article shows that TiO2 as ETL has better spectral responses from 300 nm to 900 nm wavelength compare to CdS.